2009
DOI: 10.3748/wjg.15.4356
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of insulin resistance in chronic hepatitis C

Abstract: It is now widely recognized that chronic hepatitis C (CHC) is associated with insulin resistance (IR) and type 2 diabetes, so can be considered a metabolic disease. IR is most strongly associated with hepatitis C virus (HCV) genotype 1, in contrast to hepatic steatosis, which is associated with genotype 3 infection. Apart from the well-described complications of diabetes, IR in CHC predicts faster progression to fibrosis and cirrhosis that may culminate in liver failure and hepatocellular carcinoma. More recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 103 publications
(136 reference statements)
1
57
1
2
Order By: Relevance
“…Some studies indicated that successful antiviral treatment improves insulin sensitivity in CHC patients [8,11] however, information on behavior of certain adipokines is very scarce. In our study there was no difference in serum vaspin between the pretreatment level and, at the level measured at weeks 12 and 48 (end of the therapy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies indicated that successful antiviral treatment improves insulin sensitivity in CHC patients [8,11] however, information on behavior of certain adipokines is very scarce. In our study there was no difference in serum vaspin between the pretreatment level and, at the level measured at weeks 12 and 48 (end of the therapy).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin sensitivity in CHC is affected not only by inflammation but also by a direct viral influence [5,11,20]. Some studies suggested that induction of vaspin mRNA expression in human adipose tissue could be a compensatory mechanism associated with obesity and insulin resistance [13,19,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IR has been described in several liver disorders (9,14,32,39), where it may have important clinical consequences. Thus it has been suggested that IR has a negative impact on the response rates to interferon-based therapy in chronic hepatitis C virus infection (19) and that IR could be a predictor of the presence of PH in patients with nonalcoholic fatty liver disease (16).…”
mentioning
confidence: 99%
“…Ponadto HOMA-IR był niezależ-nym czynnikiem progresji włóknienia w PZWC [13]. Stopień insulinooporności ściśle wiąże się z zasięgiem włóknienia i jego progresją [14][15][16]. Insulinooporność występowała głównie u pacjentów zakażonych genotypem 1 lub 4 i z wyższą wiremią [10,17,18].…”
Section: Wprowadzenieunclassified